Productivity Revisited : Shifting Paradigms in Analysis and Policy - Cusolito, Ana Paula; Maloney, William F. (Washington, DC: World Bank, 2018)
The stagnation of productivity in the developing world, and indeed, across the globe, over the last two decades dictates a rethinking of productivity measurement, analysis, and policy. This volume presents a 'second wave' of thinking in three key areas of productivity analysis and its implications for productivity policies.